2016
DOI: 10.15407/ujpe61.09.0780
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Quasiperiodic Metal Structures for Efficient Excitation of Surface Plasmons

Abstract: Micro-and nanostructures on the surface of silver are formed under the action of a titaniumsapphire femtosecond laser. The obtained structures are characterized by means of atomic force microscopy (AFM), multiangle light scattering, and optical spectroscopy. The excitation of surface plasmons on these structures and their effect on Raman spectra of Rhodamine 6G (R6G) dye have been studied. The enhancement of intensities of some spectral lines up to 20 times, indicating the prospects of this method of preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…For instance, the performed study of femtosecond laser surface treatment of titanium [8] has shown that laser processing the implant surfaces provides suitable surface topography, smoothing the surface with smooth microinhomogeneities and less surface contamination as compared with other treatment methods. We propose to use laser-induced periodic surface structures for application as SERS substrates [9]. Naturally, there is reasonable necessity to study physical principles corresponding to formation of surface periodic structures.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the performed study of femtosecond laser surface treatment of titanium [8] has shown that laser processing the implant surfaces provides suitable surface topography, smoothing the surface with smooth microinhomogeneities and less surface contamination as compared with other treatment methods. We propose to use laser-induced periodic surface structures for application as SERS substrates [9]. Naturally, there is reasonable necessity to study physical principles corresponding to formation of surface periodic structures.…”
Section: Introductionmentioning
confidence: 99%